Tour Guides and the Emotional Labour Nexus - Hillman, Wendy (Journal of Tourism & Adventure, 2023)
The tour guides/emotional labour nexus has only been examined since the mid-20th century and into the early 21st century. Members of an overarching tourist guide organisation were interviewed to ascertain whether or not they used emotional labour as a part of the interactive and interpretation approach with tourists. The tour guides were interviewed after in-depth engagement with the emotional labour literature, so as to determine if they used (or did not use) emotional labour in their guided tours. Participants were interviewed over a two-year timeframe at their bi-annual symposia held in remote and isolated locations. A constant comparative analysis was used to elicit themes, categories and collections from the data. Some guides did not recognise that they did in fact use emotional labour, but it referred to it in other terms. Nevertheless, it was found that emotional labour was successfully and willingly (although sometimes unwittingly) used by the tour guides in this study.